Methicillin resistant Staphylococcus aureus infection in vascular surgery patients - Garcia,Rita C. (2022)
Abstract Introduction: Surgical site infections are associated with devastating consequences in vascular surgery patients but the data on Methicillin Resistant Staphylococcus aureus (MRSA) infection among those remains scant and conflicting. Most vascular surgery antibiotic prophylaxis assume that all patients submitted to surgery are tested prior to the intervention or that all patients with risk factors for MRSA are presumed to be colonized. However, the costs associated with testing all patients are not negligible, and most of the vascular surgery patients have risk factors for MRSA colonization. The purpose of this study was to evaluate the burden of MRSA clinical infection and its outcome and to adjust clinical practice accordingly. Methods: A retrospective analysis of clinical data from all patients with MRSA isolations that were submitted to vascular surgery in the year 2019 was conducted. The primary endpoint was in-hospital mortality. Secondary endpoints were timing of infection (pre-existent infection or post-surgical infection), need for ICU and length of hospital stay. Results: Out of 1681 patients admitted for surgery in the year 2019 in the vascular surgery ward, only 21 had clinical infection with positive MRSA isolates. All the patients had risk factors for MRSA colonization. Seventeen were admitted for PAD (Rutherford grade 5 or 6). Eight patients had post-operatory infections, whilst the remaining presented with MRSA infection prior to the intervention. Post-operatory infections ranged from superficial incisional in three patients, deep incisional in one patient, and organ/space/prosthesis infection in four patients (of the last group, two had prosthesis infection). There were five deaths, of which two were unrelated to the infection. Of the three deaths probably infection-related, all were post-operatory surgical site infections, and all were organ/space/prosthesis infections (one with prosthesis infection). There was no patient admitted to the ICU that survived. The mean hospital stay was increased by 26 days (31 days, 95% CI, 19-43). Conclusion: Infection by MRSA was less frequent than expected in our population, which may mean that colonization might be smaller than expected. Pre-operative infection was almost always related to chronic wounds and did not increase the risk of post-operative wound infection or death, contrary to post-operative infection, which seems to significantly increase mortality.